Retensi Kosakata Dalam Integrasi Budaya Masyarakat Muna - Varissca Utari Tuharea; Arifandi Waikabo; Muhamad Chairul Basrun Umanailo; Muhammad Nurul Ikram Kadir (Mahesa Research Center, 2026)
Massive external linguistic pressure is currently threatening the existence of the local language and culture of the Muna people. Responding to these conditions, this study aims to examine the dynamics of retention of ancient vocabulary as an instrument of local cultural integration. This study applied a qualitative method centered on the subject's experience and memory, with data analysis using the MAXQDA 24 software. The results of the study show that the Muna people have a high capacity for retaining ancient vocabulary, which serves as a representation of cultural identity and binds group solidarity. However, this high memory retention is inversely proportional to the very minimal frequency of daily use, so its use is limited to specific and sacred contexts. To deal with the threat of language extinction, communities rely on cultural integration mechanisms through the internalization of values and media adaptation as a crucial vocabulary preservation strategy. In conclusion, the continuity of Muna culture in the contemporary era requires synergy between cultural integration at the community level and the use of public space and digital media. This is necessary to transform the preservation of ancient vocabulary from a mere object of historical memory to an active daily practice of communication.